Proceedings of the 12th Asian Internet Engineering Conference 2016
DOI: 10.1145/3012695.3012701
|View full text |Cite
|
Sign up to set email alerts
|

IP without IP addresses

Abstract: We discuss a key engineering challenge in implementing the Identifier-Locator Network Protocol (ILNP), as described in IRTF Experimental RFCs 6740-6748: enabling legacy applications that use the C sockets API. We have built the first two OS kernel implementations of ILNPv6 (ILNP as a superset of IPv6), in both the Linux OS kernel and the FreeBSD OS kernel. Our evaluation is in comparison with IPv6, in the context of a topical and challenging scenario: host mobility implemented as a purely end-to-end function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Our past work was a very basic proof of concept, based on Linux kernel v3.9, which showed that ILNP can support mobile nodes moving between two networks, with both UDP [33] and TCP [12,35]. The work reported herein extends that previous mechanism: the continuous movement scenario evaluated in Section 4 was not possible previously.…”
Section: Previous Work On Ilnp Mobilitymentioning
confidence: 65%
See 1 more Smart Citation
“…Our past work was a very basic proof of concept, based on Linux kernel v3.9, which showed that ILNP can support mobile nodes moving between two networks, with both UDP [33] and TCP [12,35]. The work reported herein extends that previous mechanism: the continuous movement scenario evaluated in Section 4 was not possible previously.…”
Section: Previous Work On Ilnp Mobilitymentioning
confidence: 65%
“…So, many of the previous analyses and experiments for ILNP have been based on mobility scenarios: both for individual mobile nodes, e.g. [12,33,34], and for whole mobile networks, e.g. [8,11,37].…”
Section: Previous Work On Ilnp Mobilitymentioning
confidence: 99%
“…The first, basic, preliminary results for TCP operation and performance of ILNP as implemented in the Linux kernel are presented in [6]. That paper shows that IPv6 applications using the sockets (2) interface can operate over ILNPv6 without being modified and at the same time offer performance that is better than MIPv6.…”
Section: Previous Work On Ilnpmentioning
confidence: 99%
“…(iv) We have shown that it is possible for an architecturally radical approach, such as ILNP, which deprecates the use of IP addresses, to be implemented directly on current systems and work across current IPv6 infrastructure. We extended our codebase from [5] allowing existing (legacy) IPv6 TCP applications to operate over ILNPv6 without modification, as initially demonstrated with some basic results in [6].…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
See 1 more Smart Citation